Finnish paramedics' professional quality of life and associations with assignment experiences and defusing use - a cross-sectional study - Christoffer R. Ericsson; Hilla Nordquist; Veronica Lindström; Ann Rudman (BMC, 2021)
Abstract Background Paramedics experience traumatic events and social emergencies during assignments while also being subjected to verbal and physical threats. Consequently, they are at risk for burnout and secondary traumatic stress, factors inherent to professional quality of life. Defusing and peer-support potentially decrease such symptoms; however, perceived defusing needs and use are not always balanced. Our aim was to explore Finnish paramedics' professional quality of life, using the Professional Quality of Life Scale, with associations to EMS assignment experiences as well as formal and informal defusing need and use over a 12-month period. Methods A quantitative study of 257 Finnish paramedics using a cross-sectional design. Study outcomes were secondary traumatic stress (STS), compassion satisfaction (CS), and burnout (BO) scores using the modified 9-item Short Professional Quality of Life scale (ProQOL). Likert-type scales were used to collect participants' recollections of assignment experiences and defusing from a 12-month period. Associations were explored using Spearman's correlation coefficients. Results Short ProQOL score medians were STS 4.00 (IQR 3), BO 6.00 (IQR 3) and CS 13.00 (IQR 3). STS and BO correlated to experiences of social emergencies and traumatic events while BO correlated to experiences of threat situations (r = 0.206, p = .001). Paramedics perceived a need for defusing in general associated with STS (r = 0.178, p < .001) and participated in informal defusing. Participation in defusing of any form did not associate with ProQOL scores. Conclusions Finnish paramedics' more frequent experiences of social emergencies, traumatic events, and paramedic-directed threat situations were associated with higher levels of STS and BO. STS was also associated with paramedics' increased need for defusing and use of informal peer defusing, although neither STS, BO or CS scores associated to any defusing form. Managing paramedics STS and BO, while fostering CS, could therefore be a future research focus.